A study of modifiable risk factors for acute lower respiratory tract infections among under five children in a tertiary care hospital in Gulbarga, Karnataka - Mirji, Gangadhar; Shashank, K J; Shrikant, S W (Indian Journal of Child Health, 2016)
Background: Acute respiratory infection includes any infection of the upper or lower respiratory system, as defined by the International Classification of Diseases. Acute respiratory infection is a leading cause of morbidity and mortality in under-five children in developing countries. Objective: This study was undertaken to identify various modifiable risk factors for acute lower respiratory tract infections (ALRI) in children aged from2 months to 5 years. Methodology: This hospital-based case–control study was conducted at Basaveshwar and Sangameshwar general hospital, Gulbarga over 1½. year 200 ALRI cases fulfilling WHO criteria for pneumonia, in the age group of 2 months to 5 years were interrogated for potentially modifiable risk factors as per a predesigned preformed. 200 healthy control children in the same age group were also interrogated. Results: The significant socio-demographic risk factors were incomplete immunization for age, low parental education, low socioeconomic status, and overcrowding (p<0.05 in all). Significant nutritional risk factors include malnutrition, anemia, and rickets (p<0.05 in all). Significant environmental risk factors were parental smoking, use of biomass fuel, and mud/cow dung flooring (p<0.05 in all). Using multiple logistic regression analysis, the factors which were found to be significantly associated were younger age (p=0.000), anemia (p=0.000), incomplete immunization for age (p=0.002), malnutrition (p=0.00), low literacy level of father (p=0.000), and overcrowding (p=0.000). Conclusion: This study has identified various socio-demographic, nutritional, and environmental modifiable risk factors for ALRI which can be tackled by effective education of the community and appropriate initiatives taken by the government.